Ag(II)-Bipyridyl Complex-Development as a Redox Titrant - Shukla, R.K.; Indrayan, A.K. (Asian Journal of Chemistry, 2010)
An acidic solution (1.0 M HNO3) of silver(II) bipyridyl nitrate is found to be suitable as a titrant for oxalic acid. Like potassium permanganate, it is a self-indicator and an advantage over permanganate is that oxidation of oxalic acid by silver(II) bipyridyl is very fast and the titration can be performed at room temperature and also in the cases where permanganate ions interfere. Results yield almost a 2% higher concentration but it being a regular feature, can be adjusted by giving a proper allowance.